1990
DOI: 10.1007/bf02126296
|View full text |Cite
|
Sign up to set email alerts
|

EEG development in early treated PKU patients from birth to 6 years of age

Abstract: In 126 early treated PKU patients (type I and type II) a close EEG follow up was performed from birth up to 6 years of age. A total of 1465 EEGs were performed before and after onset of dietary treatment and on 11 more subsequent occasions. The composition of the background activity was normal up to 6 years when only a small number of the children (19) showed no dominant alpha activity. The frequency of epileptiform activity of generalised as well as focal type was low in the first 2 years of life, but afterwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…In 1991 the progress of 51 never treated PKU patients during 22 years was reported. In that study one quarter of the patients had seizures, half were profoundly mental retarded and half were moderately impaired 16 . In our patients' group there was a positive correlation between the intensity of myelin defect and high plasma PA levels (P<0.001) (table 2).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In 1991 the progress of 51 never treated PKU patients during 22 years was reported. In that study one quarter of the patients had seizures, half were profoundly mental retarded and half were moderately impaired 16 . In our patients' group there was a positive correlation between the intensity of myelin defect and high plasma PA levels (P<0.001) (table 2).…”
Section: Discussionmentioning
confidence: 87%
“…The most common EEG abnormalities in PKU were background abnormalities and paroxysmal discharges 16,24 . In a review about EEG recording of PKU patients it was demonstrated that about 45% of the patients had an abnormal EEG and nearly 30% had a normal EEG in the beginning which became abnormal later 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…significativa. También se ha recurrido a la gamaglobulina endovenosa: Pietz y colaboradores (27) recomiendan dosis de 400 mg/kgldía por 5 días. mientras que Linder y colaboradores (28) aplican dosis más altas que permiten usar menor cantidad total de gamaglobulina, toda vez que los pacientes requieren menos aplicaciones.…”
Section: Policltemlaunclassified